The factors influencing adoption of electric vehicle among car users in Malaysia - Wee, Wen Yong; Lim, Ying Siew (2024)

(untitled)
The gradual increase in car users in Malaysia has led to an increase in carbon emissions, which has become a matter of concern. Besides, EVs have just entered the Malaysian market in recent years and can serve as an alternative to conventional cars. Therefore, the purpose of our research is to examine the factors influencing adoption of EV among car users in Malaysia. The Theory of Reasoned Action (TRA) was used in the current study to provide a conceptual framework for understanding the factors that contribute to the adoption of EV by Malaysian car users. Based on the reference model, the variable includes environmental awareness (EA), social influence (SI), and three additional variables which were charging infrastructure accessibility (CIA), government intervention (GI), and financial benefit (FB) to examine whether they have the impact adoption of EV. In addition, a total of 298 eligible respondents were successfully collected for analysis in our study. We also utilized the Statistical Package for the Social Sciences (SPSS) as the data analysis tool for our study. Moreover, the findings in this study shows that there are four of the IVs including social influence (SI), charging infrastructure accessibility (CIA), government intervention (GI), and financial benefit (FB) have a significant impact on EV adoption, while only environmental awareness (EA) has no significant impact. Finally, this study offers scholars a fresh viewpoint and a more profound comprehension of the variables influencing Malaysian car users’ adoption of EV. As a result, this study can serve as a reference for other researchers in the future.